Suppliers' Perception Of E-Sourcing Of Sanofi Synthelabo (M) Sdn. Bhd. - Ninan, George (2004)
The e-sourcing platform is an electronic purchasing system that is to be used by Sanofi-Syenthelabo to conduct purchasing activities with its suppliers. The purpose of this study is to evaluate the perception of the Malaysian suppliers in using e-sourcing to conduct business with Sanofi-Synthelabo, Malaysia.